2019
DOI: 10.9734/ijbcrr/2019/v25i430081
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile and Prevalence of Dyslipidemia in Pre- and Postmenopausal Women in Yaounde, Cameroon

Abstract: Aims: Lipids serve several important physiologic functions like energy homeostasis or biosynthesis of hormone within the human body. The deterioration of lipid metabolism which is favoured by menopause is the source of cardiovascular diseases. This study aimed to determine the plasma lipid profile and dyslipidemia prevalence of some Cameroonian women. Methodology: To achieve this goal, two sets of 105 postmenopausal and 127 premenopausal Nkeunen et al.; IJBCRR, 25(4): 1-11, 2019; Article no.IJBCRR.48605 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There have been limited studies from Nepal regarding the prevalence of dyslipidemia among post-menopausal women. A study from Cameroon showed a high prevalence of dyslipidemia at 61%, especially among females recently entering menopause [16]. Another study from Beijing also reported a high prevalence of dyslipidemia (69.7%) in postmenopausal women [17].…”
Section: Discussionmentioning
confidence: 99%
“…There have been limited studies from Nepal regarding the prevalence of dyslipidemia among post-menopausal women. A study from Cameroon showed a high prevalence of dyslipidemia at 61%, especially among females recently entering menopause [16]. Another study from Beijing also reported a high prevalence of dyslipidemia (69.7%) in postmenopausal women [17].…”
Section: Discussionmentioning
confidence: 99%